2003
DOI: 10.2214/ajr.181.5.1811341
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Conventional Sonography, Real-Time Compound Sonography, Tissue Harmonic Sonography, and Tissue Harmonic Compound Sonography of Abdominal and Pelvic Lesions

Abstract: In abdominal and pelvic scanning, tissue harmonic compound sonography provides the best overall image quality, best lesion conspicuity, and least artifacts of all the evaluated imaging modes. Spatial compound sonography is better than tissue harmonic sonography for the evaluation of lesions in general, despite some differences among lesion groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 19 publications
2
44
0
1
Order By: Relevance
“…Nowadays, new modes for acquiring sonographic images such as tissue harmonic imaging (THI) and spatial compound imaging (SCI) are widely available and have improved diagnostic performance for sonographic examinations in a variety of abdominopelvic pathologic conditions. [9][10][11][12] The aim of this study was to assess the diagnostic capabilities of sonography carried out with newer machines for showing FBWA detected on cystoscopy by means of a prospective comparison of sonographic and cystoscopic results in a population of patients referred for cystoscopic examinations.…”
mentioning
confidence: 99%
“…Nowadays, new modes for acquiring sonographic images such as tissue harmonic imaging (THI) and spatial compound imaging (SCI) are widely available and have improved diagnostic performance for sonographic examinations in a variety of abdominopelvic pathologic conditions. [9][10][11][12] The aim of this study was to assess the diagnostic capabilities of sonography carried out with newer machines for showing FBWA detected on cystoscopy by means of a prospective comparison of sonographic and cystoscopic results in a population of patients referred for cystoscopic examinations.…”
mentioning
confidence: 99%
“…In our study, no significant difference was found between RTCS and THS. Oktar et al and Yen et al, however, found RTCS to be better than THS for the elimination of artefacts in abdomino-pelvic and hepatic lesions [7][8][9]. However, a few hepatic lesions showed the presence of edge shadowing, as was seen in comparative images obtained with the use of THS.…”
Section: Discussionmentioning
confidence: 96%
“…The result is a better, more realistic image, with reduced artefacts (such as speckle), better image contrast and improved signal to noise ratio [1][2][3][4]. In recent years, its multiangled property has been shown to improve the image quality in the sonography of breast, vessels, thyroid, musculoskeletal system and abdomino-pelvic organs [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…THI and SCI) which substantially improve image quality and diagnostic yield in comparison to conventional US [23,24]; a consensus obtained between the two operators as to technical modalities of carrying out US examination of the urinary bladder; preliminary discussion of most frequently encountered pitfalls in bladder US diagnostics. On clinical grounds, this implies that well-trained and motivated operators independently of their experience may achieve high diagnostic capabilities in identifying FBWA.…”
Section: Discussionmentioning
confidence: 99%